Implementasi School Based Family Counseling (SBFC) pada Jenjang Pendidikan Anak Usia Dini - Mashudi, Esya Anesty; Nuroniah, Pepi; Fatihaturosyidah, Fatihaturosyidah (Universitas Muhammadiyah Metro, 2023)
This study aims to obtain an overview of school-based family counseling (SBFC) implementation at the early childhood education level. Using a descriptive exploratory method, data was collected through observation, scheduling, structured interviews, and documentation study techniques. The research was carried out at TK LabSchool UPI Campus in Serang. The research subjects comprised the school principal, teachers, parents of students, and counselors. The data obtained were analyzed qualitatively using an interactive model that included data display, reduction, and generalization. The study's results revealed the following findings: (1) The school-based family counseling conducted at TK LabSchool UPI Campus in Serang is a formal activity in psychotherapy intervention using a family system perspective, implemented in the school using school facilities and infrastructure. Each session is conducted in the form of a dyad (consisting of one parent and one child), a triad (two parents and one child), or a small group (two parents, one child, and one or more relatives outside the nuclear family). Counseling is carried out with attention to individual rights and informed consent, usually conducted in more than one session, and is not a parent conference or parent consultation. (2) The school must meet several requirements before implementing SBFC. (3) The study on the implementation of SBFC at the early childhood education level raises several considerations and challenges for future research.